Multi-omics mechanical analysis of gut microbiota, carboxylic acids, and cardiac gene expression interaction triggering diabetic cardiomyopathy - Meixin Shi; Bingbing Zhao; Wenjie Cai; Hui Yuan; Xiao Liang; Zhitao Li; Xinyu Liu; Ye Jin; Xi Liu; Can Wei (mSystems)
ABSTRACT It is well known that gut microbial imbalance is a potential factor for the occurrence and development of diabetes mellitus (DM) and its complications. Moreover, the heart and gut microbiota can regulate each other through the gut–metabolite–heart axis. In this study, metagenomics, metabolomics, and transcriptomics were chosen to sequence the changes in gut microbiota, serum metabolite levels, and differentially expressed genes (DEGs) in leptin receptor-deficient db/db mice and analyze the correlation between serum metabolites and gut microbiota or DEGs. According to the results, there were significant differences in the 1,029 cardiac genes and 353 serum metabolites in diabetic mice of the db/db group, including DEGs enriched in the PPAR signaling pathway and increased short-chain carboxylic acids (CAs), when compared with the normal db/m group. According to metagenomics, the gut microbiota of mice in the db/db group were disrupted, and particularly Lachnospiraceae bacteria and Oscillospiraceae bacteria significantly decreased. Also, according to the Pearson correlation analysis, a significant positive correlation was found between CAs and PPAR signaling pathway-related DEGs, and a negative correlation was found between CAs and the abundance of the above-mentioned species. To sum up, type 2 diabetes mellitus (T2DM) can upregulate the expression of partial cardiac genes through the levels of serum short-chain CAs affected by gut microbiota, thus playing a role in the occurrence and development of diabetic cardiomyopathy (DCM).IMPORTANCEOur research results clearly link the changes in heart genes of T2DM and normal mice with changes in serum metabolites and gut microbiota, indicating that some genes in biological processes are closely related to the reduction of protective microbiota in the gut microbiota. This study provides a theoretical basis for investigating the mechanism of DCM and may provide preliminary evidence for the future use of gut microbiota therapy for DCM.